The Role of Customer Satisfaction Mediates the Effect of Responsiveness on Repurchase Intention through Tokopedia in Denpasar and Badung Cities - Ardiella Myra Ananda; I Gst. Ngurah Jaya Agung Widagda K (Management Analysis Journal, 2024)
The purpose of this study was to analyze the role of customer satisfaction in mediating the effect of responsiveness on repurchase intention through Tokopedia in Denpasar and Badung Cities. Recently, Tokopedia's services have often been slow and disappointing so that customer satisfaction has decreased which can affect the decrease in repurchase intention.. This research applies a quantitative approach and is causal associative in nature. The research was conducted in Denpasar and Badung City on Tokopedia users whose numbers cannot be known with certainty (infinite population). The number of samples set at 100 respondents with a nonprobability sampling method, precisely the purposive sampling technique. The data collection method was carried out by questionnaire method using the help of Google Form and then analyzed descriptively and inferentially using path analysis techniques and the sobel test. The results of this study are found to have a positive and significant effect on responsiveness on repurchase intention, a positive and significant effect on responsiveness on customer satisfaction, a positive and significant effect on customer satisfaction on repurchase intention, and customer satisfaction which is able to mediate the effect of responsiveness on repurchase intention.